The role of polish non-governmental organizations in helping ukrainian refugees: social and economic aspects of adaptationʼ - Prykhodchenko, Liudmyla; Ivashko, Olena (Wyższa Szkoła Kadr Menedżerskich, 2024)
The article analyzes the impact of non-governmental organizations on the socio-economic well-being of Ukrainian citizens who left the country as a result of the war. The purpose of the article is to briefly summarize the experience of non-governmental organizations in Poland in assisting Ukrainian refugees during the two years of Russian aggression and to determine the specifics of the role of NGOs at the current stage of refugees' adaptation to Polish society. Ukrainians who moved to Poland after the start of Russia's full-scale invasion were assisted by human rights, psychological and legal, humanitarian, church, scouting and sports organizations, and individual artists. A study of the social, economic and cultural aspects of migration, as well as possible scenarios for the development of the situation in Poland's policy towards refugees from Ukraine, convincingly shows that their support was mainly grassroots, with social initiatives based on the involvement of individuals, social groups and NGOs. Speaking about cooperation and interaction between NGOs in Poland and Ukraine, it is worth taking into account the challenges faced by NGOs in our country, which may hinder their effective work. These include government regulation and bureaucracy, which can create barriers to registration, funding and program implementation; pressure from the authorities and inspections and audits; limited resources and funding; a complex and restrictive legal framework that limits the ability of organizations to operate freely and safely; and a lack of public trust, which can create barriers to cooperation and support from the general public. Further, issues related to competition in the labor market, overloading of the healthcare and educational systems become more urgent. Their successful resolution requires adapting requirements to opportunities, acquiring additional qualifications and gradually expanding the offerings of existing language courses, etc.
Keywords: local self-government; public authorities; public management; NGO; refugees